(untitled) (Carte Romanze, 2025)
The essay aims to study the Boccaccian novella of Nastagio degli Onesti (Decameron V 8), especially examining the value of the sources, the structure of the story, the relationship between the ideology of the author and that of his time, the overall meaning of the text and the issue of parody. In addition, the author presents a new edition of the text.